1995
DOI: 10.1093/infdis/171.5.1363
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Streptococcus pneumoniae in Neurons, Astrocytes, and Microglia In Vitro

Abstract: The toxicity of pneumococci and endotoxin in primary cultures of rat neurons, astrocytes, and microglia and in a human astrocyte and two human glial cell lines was determined. Heat-inactivated, rough pneumococci (up to 10(8) cfu/mL) or their cell wall (up to 50 micrograms/mL) produced dose-dependent toxicity after 48 h in microglial cells and to a lesser extent in astrocytes but not in neurons. Toxicity was similar for equivalent doses of heat-inactivated organisms and pneumococcal cell wall, but time-course e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 12 publications
2
21
1
Order By: Relevance
“…However, inasmuch as intraperitoneal injection of LPS at a dosage of 4 mg/kg kills newborn guinea pigs within 6 h, such mechanisms seem to be of minor importance in the present study. Nevertheless, delayed cell injury may explain some 534 discrepancies between our results and studies in adult animals and completely differentiated cell cultures in which LPSinduced injury was observed (25)(26)(27)(28)(29)(30). In addition, if LPS is exclusively toxic to a certain cell type, e.g.…”
Section: Lipopolysaccharides and Fetal Brain Damagecontrasting
confidence: 58%
“…However, inasmuch as intraperitoneal injection of LPS at a dosage of 4 mg/kg kills newborn guinea pigs within 6 h, such mechanisms seem to be of minor importance in the present study. Nevertheless, delayed cell injury may explain some 534 discrepancies between our results and studies in adult animals and completely differentiated cell cultures in which LPSinduced injury was observed (25)(26)(27)(28)(29)(30). In addition, if LPS is exclusively toxic to a certain cell type, e.g.…”
Section: Lipopolysaccharides and Fetal Brain Damagecontrasting
confidence: 58%
“…In vitro, lipopolysaccharides cause ultrastractural changes (35) and selectively depolarize (36) rodent astroglia, whereas pneumococcal cell walls selectively kill human astroglia (37). In rodents in vivo, the invading neutrophils become intimately associated with astroglia (38) and Haemophilus influenzae causes massive astroglial swelling (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings indeed demonstrated that treatment of bacterial meningitis with ␤-lactam antibiotics liberates harmful bacterial products (peptidoglycans, teichoic and lipoteichoic acids, pneumolysin) in the subarachnoid space, which results in an immediate increase in the number of active molecules that are capable of causing a rapid increase in the inflammatory response (7,10,21,28,32). In fact, the release of bacterial components, as well as host proinflammatory components and mediators, has been shown to be neurotoxic, causing apoptosis in neurons, predominantly in the dentate gyrus of the hippocampus (13,21,37). Interestingly, treatment with antibiotics such as rifampin and clindamycin, which induce (26).…”
Section: Discussionmentioning
confidence: 99%